Elementos potencialmente tóxicos em batons fabricados no Brasil - Sato, Mariane Tikae (Universidade Federal de São Carlos, 2024)
Cosmetics are products for external use that can have specific protection and/or beautification purposes for different parts of the body. Lipstick is specifically designed to hydrate, protect and color the lips, and is a product used daily by many people. Given this, it is important to analyze the quality of this product and evaluate the potential risks that the presence of toxic elements (PTEs) in lipsticks can cause to users over time. Some PTEs are related to various diseases such as skin problems, neurological, reproductive, renal, gastrointestinal and cardiovascular diseases, as well as skeletal, immune, respiratory and blood system problems. Thus, the objectives of this work were to verify the main sources of PTEs contamination in lipsticks and the effects that prolonged use of contaminated products can cause to human health; as well as determining the concentrations of PTEs in two brands of lipsticks manufactured in Brazil with red and pink colors, verifying the values in accordance with Brazilian legislation. The research methodology used to investigate the main PTEs in lipsticks, sources of contamination and effects on human health was the Systematic Literature Review (SLR). For this, the Scopus and Web of Science databases were selected for the research, using the terms “lipstick”, “heavy metals” and “potentially toxic elements”, selecting article as the type of document, open access, published in period 2013-2023, which after reading and analysis resulted in 18 articles in total. For the determination of PTEs aluminum (Al), barium (Ba), cadmium (Cd), lead (Pb), copper (Cu), chromium (Cr), strontium (Sr), iron (Fe), nickel (Ni), potassium (K) and zinc (Zn), the lipsticks samples were subjected to microwave-assisted digestion (Anton Paar) and quantified in the microwave plasma atomic emission spectroscopy (MP-AES, Agilent). Furthermore, a comparative study was carried out with masses of 0.3 g (M1) and 0.03 g (M2) of lipsticks, the M1 samples showed greater reliability in the results compared to the M2 samples. Elements such as Pb, Cu, Sr and Zn presented low concentrations, however Ba, Al, Fe and K presented high concentrations, exceeding the values allowed by Anvisa. Elements not allowed by legislation, such as Cr and Ni, had low concentrations and Cd was below the detection limit for all samples. Therefore, the results of this work show the importance of ensuring higher quality in the raw materials used in lipstick, especially mica and pigments, as well as monitoring the manufacturing and packaging process to avoid contaminations in the final product.
Potentially toxic elements in lipsticks manufactured in Brazil
Keywords: Cosméticos; Batom; Elementos Potencialmente Tóxicos; Cosmetics; Lipstick; Potentially Toxic Elements; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ANALITICA::ANALISE DE TRACOS E QUIMICA AMBIENTAL